Computational Evaluation of Redox Potentials of Metal Complexes for Aqueous Flow Batteries - Mehranfar, Aliyeh; Hannonen, Jenna; Tuna, Ali; Jafarishiadeh, Maryam; Kiesilä, Anniina; Pihko, Petri; Peljo, Pekka; Laasonen, Kari (Wiley, 2025)
Flow batteries are a promising option for large-scale stationary energy storage, but better redox active materials are required. Computational Density Functional Theory (DFT) approach to materials screening can identify the most promising avenues and accelerate the development of the technology. In this work, we focus on metal complexes with functionalized organic ligands. The right redox potential, good chemical stability, and high solubility are the main characters in designing a high-performance aqueous electrolyte. Here, Fe, Ti, Mn, and Ni are studied as central metals of the complexes with two ligand classes containing N- and O- groups. The accuracy of the DFT redox potentials is compared to experiments whenever available. In addition, some cyclic voltammetry measurements were performed for Fe-bipyridine, phenanthroline and terpyridine complexes. We have evaluated the computational redox potentials for ca.180 different metal-ligand combinations. Overall, this work presents a new insight into the design of new electrolytes for aqueous flow batteries.